PERLINDUNGAN ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA DALAM HUKUM PIDANA - Raka Palguna, Ida Bagus Putu; A. Martana, Nyoman (Kertha Wicara : Journal Ilmu Hukum, 2013)
Children is an object that become a target of domestic violence. In constitution article 34 give a big attention for children in this country but it can’t give a guarantee children is protected from violence. This paper use normatif analysis method. This paper will be explain the step of anticipation which can minimalized the violence to children and law protection for children if become domestic violence victim.
Keywords: Children, Victim, Violence